Investigation of energy absorption of a GFRP composite crash box - Ghasemnejad, Hessam; Hadavinia, H; Aboutorabi, A (WIT Press, 2008)
Interlaminar fracture toughness of composite materials plays an important role on the specific energy absorption (SEA) of the crushing of composite materials. In this regard an optimum composite crash box design is sought by studying the effect of fibre orientation and stacking sequence on the increase of interlaminar fracture toughness. In order to achieve this, various glass fibre/epoxy orientations were studied experimentally. Double Cantilever Beam (DCB) and axial crush box specimens were made and tested in a quasi-static condition to determine the interlaminar fracture toughness (GIC) and SEA values for each set of fibre orientation and stacking sequence. The effect of the stacking sequence on fracture toughness and the SEA of the GFRP composite crash box has been quantified and optimum results were obtained.
Keywords: Interlaminar fracture toughness; Specific energy absorption; Fibre orientation; Stacking sequence; Composite